Análisis de una experiencia de contenidos estadísticos con tecnología hipermedia para la formación de docentes - Chamoso Sánchez, José María (2011)
An experience using hypermedia as a tool for education of teachers is presented. More exactly, university students to become school teachers, with university computer science students, design and implement statistics topics through hypermedia with the aim that the future teachers must organize their teaching thinking in their students (both the concept intended to be worked and the form to reach the students). Results are analysed and conclusions of this work are exposed.